Trimellitic anhydride facilitates transepithelial permeability disrupting tight junctions in sinonasal epithelial cells. (15th December 2021) - Ogi, Kazuhiro; Liu, Sha; Ramezanpour, Mahnaz; Cooksley, Clare; Javadiyan, Shari; Fujieda, Shigeharu; Wormald, Peter-John; Vreugde, Sarah; Psaltis, Alkis James
Graphical abstract: Highlights: TMA attenuates transepithelial electrical resistance and increases paracellular permeability. ZO-1 and claudin-1 are disrupted by TMA in a dose-dependent manner. Trimellitic anhydride shows cytotoxicity only after prolonged incubation. Abstract: Trimellitic anhydride (TMA) is a chemical agent classified as a low molecular weight (LMW) agent causing occupational rhinitis (OR) or asthma. Although TMA is recognized as a respiratory sensitizer, the direct and non-immunologic effects of TMA remain unclear. Air- liquid interface (ALI) cultured human nasal epithelial cells (HNECs) derived from control subjects were treated with TMA, followed by measurement of the transepithelial electrical resistance (TEER), paracellular permeability of fluorescein isothiocyanate (FITC)-dextran and immunofluorescence of tight junction proteins claudin-1 and zonula occludens-1 (ZO-1). The cytotoxicity of TMA was evaluated by lactate dehydrogenase (LDH) assay. TMA at concentrations of 2 and 4 mg/mL significantly reduced the TEER within 10 min (p = 0.0177 on 2 mg/mL; p < 0.0001 on 4 mg/mL). The paracellular permeability of FITC-dextran was significantly increased upon challenge with 4 mg/mL TMA for 3 h (p = 0.0088) and 6 h (p = 0.0004). TMA treatment induced a reduction in the fluorescence intensity of claudin-1 and ZO-1 in a dose-dependent manner. LDH assay revealed 4 mg/mL TMA induced cytotoxicity only after 6 h incubation, while 1 or 2 mg/mL TMA caused no cytotoxicity. Our results suggest that TMA has a potential to penetrate the epithelial barrier by disrupting claudin-1 and ZO-1, indicating an important role for sensitization and OR development.